Analisis Peran Green Zakat dalam Pengentasan Kemiskinan dan Keberlanjutan Ekonomi di Indonesia: Studi Komparatif Data Sekunder 2025 - Rika Yuliastuti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines the role of Green Zakat in poverty alleviation and economic sustainability in Indonesia through a qualitative comparative approach based on secondary data from 2025. Green Zakat represents an innovative integration of Islamic social finance with principles of the green economy and sustainable development. By analyzing patterns of zakat distribution, sustainable financing initiatives, and emerging policy frameworks, the study explores how this model expands the traditional function of zakat beyond short-term charitable relief toward long-term socio-economic and environmental impact. The findings reveal that Green Zakat contributes to poverty reduction by promoting productive economic empowerment, supporting environmentally responsible livelihoods, and enhancing financial inclusion among vulnerable communities. Furthermore, the framework strengthens the linkage between Islamic philanthropy and sustainable finance, encouraging resource allocation that aligns with climate resilience and social equity goals. Institutional collaboration between zakat agencies, Islamic financial institutions, and development organizations also appears to be a key factor in maximizing impact. Overall, Green Zakat demonstrates strong potential as a strategic instrument for inclusive and environmentally conscious economic development, offering valuable insights for researchers, practitioners, and policymakers seeking to optimize the role of Islamic social finance in achieving sustainable development objectives.